Screening of Polyalthia longifolia and Aloe vera for their phytoextractability of heavy metals in tropical soil of the Niger Delta - FBG Tanee; N Amadi (Journal of Applied Sciences and Environmental Management)
The work focuses on the screening of Polyalthia longifolia and Aloe vera for their phytoextractability of  heavy metal in soil of the Niger Delta. 5kg of soil was polluted with 100 mg of Zn, Fe and Pb each  replicated 9 times. Each set was separated into 3 subgroups. The subgroups were phytoextracted with Polyalthia longifolia and Aloe vera alongside a control (no phytoextraction) respectively. After 12 weeks, the concentration of Lead, Iron and Zinc in soils, roots and shoots was determined. Results showed that the two plants have phytoextraction ability with reductions in Zn, Fe, and Pb in the phytoextraction soil . Metal transfer factor was PB: Aloe vera (0.881) > P. longifolia (0.315); Zn: P. longifolia (0.614) > Aloe vera (0.606); Fe: Aloe vera (0.812) > P. longifolia (0.774). Translocation factors for the two plants were in the order: Zn: P. longifolia (0.79) > Aloe Vera (0.36); Fe: P. longifolia (0.63) > Aloe Vera (0.05); Pb: P. longifolia (0.57) > Aloe Vera (0.23). Since the translocation factors were < 1, the plants can be classified as non- hyperaccumulators for these metals. © JASEM